Two Different Replication Factor C Proteins, Ctf18 and RFC1, Separately Control PCNA-CRL4(Cdt2)-Mediated Cdt1 Proteolysis during S Phase and following UV Irradiation - Shiomi, Yasushi (American Society for Microbiology, 2012)
Recent work identified the E3 ubiquitin ligase CRL4(Cdt2) as mediating the timely degradation of Cdt1 during DNA replication and following DNA damage. In both cases, proliferating cell nuclear antigen (PCNA) loaded on chromatin mediates the CRL4(Cdt2)-dependent proteolysis of Cdt1. Here, we demonstrate that while replication factor C subunit 1 (RFC1)-RFC is required for Cdt1 degradation after UV irradiation during the nucleotide excision repair process, another RFC complex, Ctf18-RFC, which is known to be involved in the establishment of cohesion, has a key role in Cdt1 degradation in S phase. Cdt1 segments having only the degron, a specific sequence element in target protein for ubiquitination, for CRL4(Cdt2) were stabilized during S phase in Ctf18-depleted cells. Additionally, endogenous Cdt1 was stabilized when both Skp2 and Ctf18 were depleted. Since a substantial amount of PCNA was detected on chromatin in Ctf18-depleted cells, Ctf18 is required in addition to loaded PCNA for Cdt1 degradation in S phase. Our data suggest that Ctf18 is involved in recruiting CRL4(Cdt2) to PCNA foci during S phase. Ctf18-mediated Cdt1 proteolysis occurs independent of cohesion establishment, and depletion of Ctf18 potentiates rereplication. Our findings indicate that individual RFC complexes differentially control CRL4(Cdt2)-dependent proteolysis of Cdt1 during DNA replication and repair.